Transformational Leadership of Administrators That Affects Learning Organization in Schools under the Office of the Private Education Commission, Chatuchak District, Bangkok - พึ่งอ่ำ, พิไลพร; ประวัติรุ่งเรือง, ปราศรัย; แก้วมงคล, ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) to examine the level of transformational leadership of school administrators, 2) to investigate the level of learning organization in educational institutions, 3) to study the relationship between transformational leadership of administrators and learning organization in educational institutions, and 4) to analyze transformational leadership factors affecting learning organization in educational institutions under the Office of the Private Education Commission, Chatuchak District, Bangkok. The sample consisted of 239 teachers from educational institutions under the jurisdiction of the Office of the Private Education Commission in Chatuchak District, Bangkok. The sample size was determined using Yamane’s formula, and stratified random sampling was employed based on school size, followed by proportional allocation and simple random sampling. The research instrument was a five-point rating scale questionnaire with an index of item-objective congruence (IOC) ranging from 0.80 to 1.00 and a reliability coefficient of .996. The statistical methods used for data analysis included frequency, percentage, mean, standard deviation, Pearson’s product–moment correlation coefficient, and stepwise multiple regression analysis.           The research findings indicated that: 1) The overall level of transformational leadership of administrators was at a high level. 2) The overall level of learning organization in educational institutions was at a high level. 3) Transformational leadership and learning organization were highly correlated (r = 0.976), with statistical significance at the .01 level. and 4) Transformational leadership variables were identified as significant predictors of learning organization, ranked in order of importance as follows: intellectual stimulation (X3, b = 0.365), inspirational motivation (X2, b = 0.232), individualized consideration (X4, b = 0.229), and idealized influence (X1, b = 0.193). The predictive equations for learning organization were as follows.               Raw score equation: Y=.095+.361X3+.215X2+.216X4+.187X1               Standardized score equation: ZY=.365X3+.232X2+.229X4+.193X1